2008
DOI: 10.1103/physrevd.78.064056
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational wave burst signal from core collapse of rotating stars

Abstract: We present results from detailed general relativistic simulations of stellar core collapse to a protoneutron star, using two different microphysical nonzero-temperature nuclear equations of state as well as an approximate description of deleptonization during the collapse phase. Investigating a wide variety of rotation rates and profiles as well as masses of the progenitor stars and both equations of state, we confirm in this very general setup the recent finding that a generic gravitational wave burst signal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
441
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(473 citation statements)
references
References 76 publications
(214 reference statements)
29
441
3
Order By: Relevance
“…Thus the time scale for collapse is τ FF ∼ 2 ms and the frequency of GWs would be f ∼ τ −1 FF ∼ 500 Hz. Numerical simulations also reveal that the time domain waveform is a short burst and the energy in the burst is spread over a frequency range of 200 Hz to 1 kHz, with the peak of the radiation at f peak 500 Hz [429,430]. If a fraction ∼ 10 −8 of the rest mass energy of the star is converted to GWs then the characteristic amplitude of the signal would be h c ∼ 2 × 10 −22 Hz −1/2 .…”
Section: A Menagerie Of Neutron-star Sourcesmentioning
confidence: 99%
“…Thus the time scale for collapse is τ FF ∼ 2 ms and the frequency of GWs would be f ∼ τ −1 FF ∼ 500 Hz. Numerical simulations also reveal that the time domain waveform is a short burst and the energy in the burst is spread over a frequency range of 200 Hz to 1 kHz, with the peak of the radiation at f peak 500 Hz [429,430]. If a fraction ∼ 10 −8 of the rest mass energy of the star is converted to GWs then the characteristic amplitude of the signal would be h c ∼ 2 × 10 −22 Hz −1/2 .…”
Section: A Menagerie Of Neutron-star Sourcesmentioning
confidence: 99%
“…In particular the infall and bounce phases, which are theoretically relatively well understood parts of the evolution, have received a lot of interest, because a strong and characteristic signature could make them a promising source of a detectable gravitational-wave burst (for a review-like introduction to the subject and a nearly complete list of publications, see Dimmelmeier et al 2008). For this to be the case, the core of the progenitor star must develop a sufficiently large deformation during its infall, and for that it must rotate enough rapidly.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…Of the entire ensemble of potential GW emission processes in stellar collapse, rotating core collapse and bounce is arguably the simplest and yields the cleanest signal, depending only on rotation, on the nuclear EOS, and on the mass of the inner core at bounce [5]. Moreover, 3D studies have shown that collapsing iron cores with rotation rates in the range of what is physically plausible stay axisymmetric throughout the collapse phase and develop nonaxisymmetric dynamics only after bounce [4,6,17].…”
Section: Introductionmentioning
confidence: 99%
“…Rotation, centrifugally deforming the inner core to oblate shape, is an obvious source of such quadrupole asymmetry and rotating core collapse and bounce is the most extensively studied GW emission process in stellar collapse (see, e.g., [4][5][6][7][8][9] for recent studies and references therein). Alternatively, asymmetries in collapse may arise from perturbations, e.g., due to large convective plumes in the final phase of core nuclear burning, and may lead to GW emission at bounce and/or seed GW-emitting prompt postbounce convection [3,10,11].…”
Section: Introductionmentioning
confidence: 99%